Talk Therapy and Human Capital in Adolescence: Evidence from a Low-Resource Setting - Eric Edmonds; Priya Mukherjee; Nikhilesh Prakash; Nishith Prakash; Shwetlena Sabarwal (CESifo GmbH, 2025)
We evaluate the impact of a therapy intervention on Nepali adolescents at risk of dropping out of school. Our randomized controlled trial is the largest of its kind (N = 1,707) and is novel in that participation does not require a preexisting diagnosis. Participation was high: 89 percent of adolescents offered therapy attended, with younger participants showing higher compliance. Therapy significantly reduced psychological distress, improved emotional regulation, and enhanced perspectives on life. These psychological benefits did not translate into better school attendance or cognitive outcomes. Our results indicate that mental health interventions alone may not be sufficient to improve educational performance in low-resource environments.
Keywords: H25; F23; M48; H26; 330; teen mental health; education; therapy; Nepal